Real social science : applied phronesis - Flyvbjerg, Bent.; Landman, Todd.; Schram, Sanford (Cambridge, U. K. : Cambridge University Press, 2012)
'Real Social Science presents a new, hands-on approach to social inquiry. The theoretical and methodological ideas behind the book, inspired by Aristotelian phronesis, represent an original perspective within the social sciences, and for the first time this volume gives readers a set of studies exemplifying what applied phronesis looks like in practice. The reflexive analysis of values and power gives new meaning to the impact of research on policy and practice. Real Social Science is a major step forward in a novel and thriving field of research. This book will benefit scholars, researchers, and students who want to make a difference in practice, not just in the academy. Its message will make it essential reading for students and academics across the social sciences'--
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Philosophy